2018
DOI: 10.1002/ps.5062
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐mediated RNAi of grain aphid CHS1 gene confers common wheat resistance against aphids

Abstract: These results indicate that plant-mediated RNAi of the grain aphid CHS1 gene confers common wheat resistance against aphids. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
2
31
0
1
Order By: Relevance
“…However, in soybean aphid (A. glycines Matsumura), the mRNA transcription of CHS1 gene was highest in the nymphal stage (second instar) [41]. Similarly, the peak expression level of CHS1 was also detected during developmental stages of grain aphid (Sitobion avenae) [39]. In the present study, transcripts of CHS1 gene were perceived in all life stages of A. gossypii; however, the highest expression was observed in the first-instar nymph.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…However, in soybean aphid (A. glycines Matsumura), the mRNA transcription of CHS1 gene was highest in the nymphal stage (second instar) [41]. Similarly, the peak expression level of CHS1 was also detected during developmental stages of grain aphid (Sitobion avenae) [39]. In the present study, transcripts of CHS1 gene were perceived in all life stages of A. gossypii; however, the highest expression was observed in the first-instar nymph.…”
Section: Discussionsupporting
confidence: 41%
“…CHS1 is expressed in the epidermal cells encoding enzymes that are essential for the catalysis of chitin production in cuticle [36,37], while CHS2 is expressed in the peritrophic membrane regulating enzymes for chitin production in insect midgut [38]. Several studies reported that CHS1 gene is crucial for chitin synthesis in aphid molting [39][40][41]. However, due to lacking peritrophic membrane, CHS2 was not existent in some insects [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, given the level of sequence divergence between the corresponding M. persicae genes and the Be. tabaci ecdysone receptor and P. solenopsis chitin synthase constructs (Table S1), the RNAi effects on the expression levels of these genes are likely to be more minor than those observed with M. persicae cathepsin L. Moreover, we did not observe the morphological phenotypes that were previously reported when silencing ecdysone receptor or chitin synthase expression (Zhu et al , ; Khan et al , ; Shang et al , ; Yan et al , ; Vellichirammal et al , ; Zhao et al , ), and the identified protein accumulation deficit is more similar to what one would expect from silencing the expression of a gut protease.…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, a C ‐> U mismatch at such a position is predicted to have a severe effect on RNAi efficiency (Ahmed and Raghava, ). Previous experiments involving expression silencing of chitin synthase in aphids and mealybugs resulted in physical deformities and/or the inability to moult (Khan et al , ; Shang et al , ; Zhao et al , ). We did not observe such morphological effects in our M. persicae experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The production of transgenic plants is another strategy to deliver dsRNA for inset pest control. A number of studies have used this approach to develop transgenic plants expressing dsRNA against insects in the order Hemiptera [40][41][42], Coleoptera [17,[43][44][45], or Lepidoptera [16,46,47]. However, transgenic plant-mediated RNAi based on conventional nuclear transformation technology did not offer efficient protection from insect damage, probably due to (i) low expression of dsRNA and (ii) instability of dsRNAs (result from plants' endogenous Dicer cleavage) in planta [14].…”
Section: Discussionmentioning
confidence: 99%